Thermal balance sheet of alternative fuel on a single cylinder DI engine - Karn, Rupesh Lal; Aryal, Suman; Neupane, Barsha; Koirala, Manish; Palikhel, Laxman (Journal of Innovations in Engineering Education, 2021)
An internal combustion engine can be considered a thermodynamic open system. Investigation on blends of distilled plastic oil was performed on a constant speed diesel engine at various loading conditions. The thermal balance sheet was prepared concerning useful work i.e. heat equivalent to useful work, heat loss in jacket cooling water, heat loss in the exhaust gas, and unaccounted heat i.e. heat loss in radiation. Blends up to 20% by volume of various high-grade plastic fuels were used. The thermal balance sheet indicates that heat equivalent to brake power of 5PDB is higher than diesel at low load and 10PDB has higher HBP than diesel at high load. All blends of PDB indicate higher heat conversion into useful work. The exhaust gas temperature of all blends of high-grade plastic fuel is lower than that of diesel which shows a better conversion rate of produced heat in the cylinder into useful work.